Αντίο παλιέ κόσμε : συνομιλίες με αξιοσημείωτους ανθρώπους - Τσαγκαρουσιάνος, Στάθης (Δρομέας, 1999)
Χριστιανόπουλος -- Χατζιδάκις -- Πεντζίκης -- Χατζηκυριάκος-Γκίκας -- Γλυκατζή- Αρβελέρ -- Θεοδωράκης